(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objective: A case report on the treatment of necrotizing fasciitis with the use of high frequency (HF) generator in a person with diabetes. Methods: This is descriptive study of applied nature developed in an outpatient clinic in Minas Gerais. The patient underwent dressing sessions three times a week for high frequency application. Healing was weekly evaluated using the Pressure Ulcer Scale Healing (PUSH) instrument and Image J software. Results: The area was significantly reduced, which was measured during six weekly evaluations. In the first four evaluations, a progressive reduction of the lesion was obtained in 11.78 cm², that is, 90% of the area. Conclusion: The use of the AF generator was effective in the treatment of necrotizing fasciitis, reducing the lesion area.